On some low separation axioms in bitopological spaces - M. L. Thivagar; S. A. Ponmani; S. Jafari; M. Caldas (Boletim da Sociedade Paranaense de Matemática, 2006)
Recently, in 2003, Caldas et al. [1] introduced the notions of A_{delta}-T_i and A_{delta}-R_i topological spaces for i = 1; 2 as a version of the known notions of T_i and R_i (i = 1;2) topological spaces [8] and [2]. In this paper, we extend A_{delta}-T_i and A_{delta}-R_i to bitopological spaces for i = 1;2 and define the notions of pairwise A_{delta}-T_i and A_{delta}-R_i bitopological spaces for i = 1;2. In this context, we study some of the fundamental properties of such spaces. Moreover, we investigate their relationship to some other known separation axioms.